Ecopoetics in Yorùbá Riddles - Olumide Adegbodu (Yoruba Studies Review)
In contemporary literary scholarship, assumes that certain subject matters are bourgeoning in literary texts produced recently. For instance, the motif of environment/ecosystem seen to be novel in literary representations. However, Africans, long before their contact with coloniality, have engaged their literary texts in interrogating various aspects of their cultural milieu, including the ecosystem. One of the ecocentric poetic genres of Yorùbá literature is àlọ́ àpamọ̀ (riddles). This study, therefore, investigates the representations of interactions among different stakeholders of the ecosystem in selected àlọ́ àpamọ̀. The study reveals that Yorùbá riddles are fraught with ecocritical consciousness. Images of the environment in the discussed riddles emphasize man’s inseparable relationship with the environment or ecosystem. Similarly, the anthropocentric nature of man depicts that man and nature cannot be separated as they are mutually interactive.